2020
DOI: 10.23925/2237-4418.2020v35i1p15-32
|View full text |Cite
|
Sign up to set email alerts
|

Comportamento Do Consumidor Voltado Para a Sustentabilidade: Elucidando O Campo Teórico E Contribuindo Para Agenda De Pesquisa

Abstract: O estudo buscou revisitar as principais abordagens teóricas existentes na literatura sobre o comportamento do consumidor voltado para a sustentabilidade organizando o conhecimento do campo de estudo e apresentar contribuições para o desenvolvimento de uma agenda de pesquisa na referida área. Ao analisar trabalhos que exploram o tema do comportamento do consumidor e construir um apanhado histórico da área, foi possível fornecer uma perspectiva teórica na qual a pesquisa sobre comportamento do consumidor tem se … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 20 publications
0
5
0
1
Order By: Relevance
“…The concern with identifying and understanding who the green consumer is and what their characteristics are began in the 1970s. There was a belief that the profile of the green consumer would be young women, with higher incomes, who lived in urban areas and who had a higher level of education, however there was never a consensus on this profile, as many other studies found little relationship with demographic characteristics (Pivetta et al, 2020). Some authors propose the segmentation of sustainable consumers based on psychographic characteristics.…”
Section: Green Marketing Strategies Greenwashing and Segmentationmentioning
confidence: 99%
“…The concern with identifying and understanding who the green consumer is and what their characteristics are began in the 1970s. There was a belief that the profile of the green consumer would be young women, with higher incomes, who lived in urban areas and who had a higher level of education, however there was never a consensus on this profile, as many other studies found little relationship with demographic characteristics (Pivetta et al, 2020). Some authors propose the segmentation of sustainable consumers based on psychographic characteristics.…”
Section: Green Marketing Strategies Greenwashing and Segmentationmentioning
confidence: 99%
“…The subject of consumer behaviour can be introduced as an area of study covering different disciplines, since it is influenced by different sciences. Based on Pivetta et al (2020) [94], various economists gave rise to the first studies on consumer behaviour, such as Adam Smith, who considered human needs to be innate and consumption decisions to be rational, based on evaluating the usefulness of products.…”
Section: Consumption and Consumer Behaviourmentioning
confidence: 99%
“…Since then, interest in studies in the area of consumer behaviour has grown considerably. According to data from the Web of Science database on publications on this subject, the number of studies tripled between 2007 and 2017 [94].…”
Section: Consumption and Consumer Behaviourmentioning
confidence: 99%
See 1 more Smart Citation
“…Nabiv (2020) a define como a gestão das atividades humanas sob o prisma da questão ambiental. Neste sentido, Pivetta et al (2020) propõem que haja uma reformulação no conceito de desenvolvimento, destacando que ele deve ser entendido como a apropriação efetiva de todos os direitos humanos, políticos, culturais, sociais e o direito coletivo ao meio ambiente.…”
Section: Sustentabilidade Ambiental No Contexto Mercadológicounclassified